Pengaruh Motivasi Kerja, Dispilin Kerja, dan Loyalitas Terhadap Kinerja Tenaga Keperawatan Rumah Sakit Muhammadiyah Palembang - Hasan Pratama Putra; Miuhammad Idris; choriyah Choiriyah (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2023)
This study aims to determine the effect of motivation, discipline, and work loyalty on the performance of nursing staff at Muhammadiyah Palembang Hospital. The effect of motivation on performance, the effect of discipline on performance, and the effect of work loyalty on the performance of nursing staff at Muhammadiyah Palembang Hospital. This type of research is quantitative descriptive and verification. The data source used in this study was the nursing staff of Muhammadiyah Palembang Hospital. Based on the research objectives, the method used in this study is a data analysis technique using multiple linear regression analysis. This analysis was used to measure the influence of the independent variables, namely motivation, discipline, and loyalty on the dependent variable, namely the performance of 112 nursing staff at Muhammadiyah Palembang Hospital. The results of this study indicate that motivation, discipline, and loyalty together have a significant positive effect on the performance of nursing staff at Muhammadiyah Palembang Hospital. Motivation has a significant positive effect on the performance of nursing staff at Muhammadiyah Palembang Hospital. Discipline has a significant positive effect on the performance of nursing staff at Muhammadiyah Palembang Hospital. Loyalty has a significant effect on the performance of nursing staff at Muhammadiyah Palembang Hospital.